2014
DOI: 10.1123/jpah.2012-0064
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Schoolyard Features and Behavior Patterns in Children’s Utilization and Physical Activity

Abstract: This work suggests that the inclusion or omission of specific playground features may have an impact on the way that children use the spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…A study of primary school children in Germany showed that attractively designed school playgrounds were positively related to girls’ regular overall physical activity (Möhrle et al 2015). Additionally, Anthamatten et al (2014) showed that girls were more likely to play in playground zones with equipment while boys were more active in those without equipment, such as playing field areas. Other studies have also observed gendered activities in playgrounds (Paechter and Clark 2007): Girls preferred playing with, at or inside play objects like huts, and boys preferred ball games such as soccer and tended to occupy larger spaces than girls did.…”
Section: Discussionmentioning
confidence: 99%
“…A study of primary school children in Germany showed that attractively designed school playgrounds were positively related to girls’ regular overall physical activity (Möhrle et al 2015). Additionally, Anthamatten et al (2014) showed that girls were more likely to play in playground zones with equipment while boys were more active in those without equipment, such as playing field areas. Other studies have also observed gendered activities in playgrounds (Paechter and Clark 2007): Girls preferred playing with, at or inside play objects like huts, and boys preferred ball games such as soccer and tended to occupy larger spaces than girls did.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of schools in New Zealand found an association between a greater number of fixed play equipment on school grounds and higher levels of physical activity in children [49]. Thus, outdoor play equipment may increase children’s physical activity at school [50], although there is some evidence that girls are more likely than boys to utilize playground equipment [51]. However, given that these previous studies were conducted in high-income countries, additional information is needed to evaluate outdoor play equipment and children’s physical activity within a low-middle income country like India.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, because we used vertical accelerations of the hip to assess PA, it is likely that the intensity (energy expenditure) of PA involving substantial upper-body movements, such as climbing, was underestimated (Lee and Shiroma, 2013). Lastly, we do acknowledge that landscape features, such as areas with a naturalistic feel and areas with different surfaces, may influence the PA level of children (Anthamatten et al, 2014; Fjørtoft, 2004). Because of the risk of overfitting the regression models, we chose not to adjust for this.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies indicate that girls and boys use different areas of their school's outdoor play area (SOPA) when being physically active (Fjørtoft et al, 2009; Anthamatten et al, 2014), that PA levels are higher in areas with a naturalistic feel (Fjørtoft, 2004) and that colorful playground markings can increase recess PA (Blaes et al, 2013). Both the size of SOPA and the availability of permanent play facilities (PPF) are basic components of a schoolyard design, and studies indicate that both factors may be important to stimulate PA (D'Haese et al, 2013; Escalante et al, 2012; Nielsen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%